2018
DOI: 10.1139/cjm-2017-0532
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis to deactivate two nitrogenase isozymes of Kosakonia radicincitans DSM16656T

Abstract: Biological nitrogen fixation (BNF) is considered one of the key plant-growth-promoting (PGP) factors for diazotrophic organisms. Whether the iron and iron-molybdenum nitrogenases of Kosakonia radicincitans contribute to its PGP effect is yet to be proven. Hence, for the first time, we conducted site-directed mutagenesis in K. radicincitans to knock out anfH and (or) nifH as a mean to deactivate BNF in this strain. We used N-labeled air to trace BNF activities in ΔanfH, ΔnifH, and ΔanfHΔnifH mutants. Assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This result was also reported for the strain Rhodopseudomonas palustrus, a diazotrophic bacterium that contains three types of nitrogenases (Oda et al 2005). Recently, it was reported that the nitrogenase mutants ΔnifH and ΔanfHΔnifH in the plant-associated strain K. radicincitans DSM16656 T were impaired in their ability to fix nitrogen (Ekandjo et al 2018). The strain DSM16656 T has 98.91% genome similarity to the UYSO10 strain, and both strains have exactly the same nitrogenase nif and anf operon arrangement with almost 100% aa identity sequences.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This result was also reported for the strain Rhodopseudomonas palustrus, a diazotrophic bacterium that contains three types of nitrogenases (Oda et al 2005). Recently, it was reported that the nitrogenase mutants ΔnifH and ΔanfHΔnifH in the plant-associated strain K. radicincitans DSM16656 T were impaired in their ability to fix nitrogen (Ekandjo et al 2018). The strain DSM16656 T has 98.91% genome similarity to the UYSO10 strain, and both strains have exactly the same nitrogenase nif and anf operon arrangement with almost 100% aa identity sequences.…”
Section: Discussionsupporting
confidence: 76%
“…S2). Nevertheless, the nitrogenase activity of strain UYSO10 was not significantly affected by the presence or absence of Mo, as was reported for strain DSM16656 T (Ekandjo et al 2018) and other diazotrophic strains such as R. palustris and Rhodospirillum rubrum (Lehman and Roberts 1991;Oda et al 2005). This is not the case for the strains A. vinelandii and R. capsulatus, where a Mo concentration of 1 μM or 10 nM inhibits the expression of the alternative nitrogenases (Joerger et al 1990;Schneider et al 1991), suggesting a diverse regulation mechanism process.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Whereas, nifHDK of K. radicincitans encodes a component of the iron–molybdenum (FeMo) nitrogenase, which is found in all diazotrophs, its anfHDGK encodes for a component of the iron-only (Fe) nitrogenase found secondarily in only some diazotrophs (Ekandjo et al, 2017). In conformity with two nitrogenase gene clusters there are also two genetic components for regulatory cascades controlling nif transcription in K. radicincitans .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the presence of fixJL and nod D genes suggests that N 2 -fixation of DSM 16656 T is affected by plants and O 2 concentration. Ekandjo and co-workers could not detect significant contribution of the Fe nitrogenase to biological dinitrogen assimilation under pure bacterial culture experimental conditions but speculated that having both nitrogenases might enable K. radicincitans to fix atmospheric nitrogen in different environments, however fixation of atmospheric nitrogen in planta was not studied (Ekandjo et al, 2017). Our microscopic analyses of DSM 16656 T colonizing root parenchyma cells of plants (Figure 7) suggest that enteric bacteria may be capable of generating their own microaerobic niche for atmospheric nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%